KONTRIBUSI KESADARAN DIRI (SELF-AWARENESS) DAN HARAPAN (HOPE) TERHADAP CAREER ADAPTABILITY MAHASISWA - Triani Arfah; Ince Prabu Setiawan Bakar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract: Contribution of Self-Awareness and Hope to Student Adaptability Career. This study aims to look at the contribution of self-awareness and self-hope to student career maturity. The research approach uses a quantitative approach. The research independent variables are hope and self-awareness. While the dependent variable in this study is career maturity. Data analysis using simple regression, to see the contribution of independent variables (self-awareness and Hope) to the career maturity of students. The scale in this study uses an adaptation scale from SAQ (Golman, 1995) and Hope (Snayder, 1997). CFA test results indicate that the career maturity scale has Croanbach's Alpha .880. As for SAQ. 817, and Hope Scale .5050. The sample in this study were 138 Islamic University students in Makassar. The sampling technique used in this study is random sampling where samples are randomized simply. The results of this study indicate that self-awareness and expectations together contribute to student career maturity, with a significant level of .000. This variable affects 42.2% of the career maturity variable and the remaining 57.2% is due to other factors not measured in this study. Meanwhile, F = 49,043 and a significance level of 0,000 indicates that the contribution of Self awareness and Hope influences thecareer maturity of students